Dividend Payout Ratio in Indonesian Consumer Goods Industry: Panel Analysis and Determinant Factors in 2004-2013 - Sinabutar, Alexander; Nugroho, Anggoro Budi (Journal of Business and Management, 2015)
Abstract- Many study about dividend policy has been done, but still being a contradiction until now. This research conducted to know the determinant factors of dividend payout ratio in Indonesian consumer goods industry sector between 2004 and 2013. There are several factors selected in this research, such as return on assets, debt to equity ratio, current ratio, market to book value, sales growth and firm size. In order to identify the relationship between selected factors with dividend payout ratio, author conduct assumption test and panel regression analysis toward the collected data. Research result shows that return on assets, debt to equity ratio, current ratio, market to book value, sales growth and firm size simultaneously have significant effect on dividend payout ratio. The result also shows that return on assets, current ratio, market to book value and firm size have a positive relationship on dividend payout ratio. While sales growth and debt to equity ratio have a negative relationship on dividend payout ratio. However sales growth is the only factor that significantly affect dividend payout ratio. Besides that research result shows that the value of adjusted r-squared is 64.46%.Â Keywords: Dividend Payout Ratio (DPR), Return on Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), Market to Book Value (MBV), Sales Growth, Firm Size, Consumer Goods Industry